THE INFLUENCE OF GUIDED QUANTUM MODEL APPLICATION TOWARD SOCIAL STUDIES ACHIEVEMENT REVIEWED FROM THE PARTICIPATION ON THE FOURTH GRADE STUDENTS SDN 2 SOKARAJA TENGAH - Inkamawarni, Elsa Okti; Pamujo, Pamujo; Harmianto, Sri (Universitas Muhammadiyah Purwokerto, 2014)
The purposes of this study were: 1) know the influence from the guided quantum model toward sosial studies achievement, 2) know the influence of the participation toward the sosial studies achievement, 3) the interaction using the guided quantum model, direct learning model and studentâs participation toward the sosial studies achievement. This type of research is experimental research. The sampling that used in this research is the cluster random sampling technique. The population were the fourth grade students of SDN 2 Sokaraja Tengah that consist of two class, thereâs IV A class as the experiment class and the IV B class as the control class. The sampling in the IV A class using the guided quantum model and the IV B class using direct learning model. The sampling is used a test and questionnaire. The data analysis is used two lane variance analysis. The result showed that, 1) the guided quantum model has an influence to studentâs sosial studies achievement that proved with Fcolumn = 4,698> Ftable = 4,02significance column 0,048<0.05, 2) thereâs an participation influence to the students achievement that proved Flane = 4,828> Ftable = 4,02Â significance line 0,030< 0,05, 3) thereâs no interaction between guided quantum model, direct learning and students participation toward sosial studies achievement that proved Finteraction = 0,828< Ftable = 4,02Â interaction significance0,166> 0,05.Â 193Â 193Â 196Â KeywordÂ Â Â Â Â Â Â : Academic Achievement, Guided Quantum Model, Participation